EP 83. Neural correlates of age-related changes in cognitive action control. Issue 9 (September 2016) - Latz, A.; Hoffstädter, F.; Cieslik, E.; Caspers, S.; Amunts, K.; Moebus, S.; Pundt, N.; Eickhoff, S.; Langner, R.
Abstract : Introduction: Healthy aging has been associated with a decrease in cognitive action control, but the underlying neural mechanisms are still elusive. The spatial stimulus-response compatibility (SRC) task captures this aspect of cognitive control, as it requires overcoming predominant but incorrect action tendencies to enable correct responding. Aim: To identify brain areas that change their action-control-related activity with age. Methods: Using fMRI we measured brain activity in a large sample of adults recruited from the population-based 1000BRAINS study ( n = 234; mean age 52.5 years; 130 males) while performing an SRC task. Participants were instructed to give a speeded response to lateralized visual stimuli with the ipsilateral (spatially compatible) or contralateral (spatially incompatible) hand. Effects of incompatibility and age on performance [reaction time (RT) and error rate (ER)] were tested via an analysis of covariance (ANCOVA) with compatibility as within-subject factor and age as covariate. Effects on brain activity were also tested via an ANCOVA, additionally including as covariate the behavioral incompatibility effect (ICE; i.e., the difference between mean RT in incompatible and compatible trials). Results: RT and ER globally increased under incompatibility, and the increase in RT became larger with advancing age as indicated by a significant interaction effect. Neurally, we observed incompatibility-related activity bilaterally in dorsolateral prefrontal cortex (DLPFC), premotor cortex (PMC), intraparietal sulcus (IPS) and adjacent inferior and superior parietal lobule (IPL/SPL), anterior insula, (pre-)supplementary motor area [(pre)SMA] extending into midcingulate cortex (MCC), and cerebellum. Age-related hyper-activity in this network was restricted to bilateral DLPFC and cerebellum. In turn, a significant association with the behavioral ICE was found in the left IPS and SPL. Thus, while older adults showed a stronger recruitment of the cerebellum and DLPFC, high-ICE performers showed a stronger recruitment of the IPS/SPL. Conclusion: We here replicated the significant increase of incompatibility costs with age (Langner et al., 2014 ) in a substantially larger sample. Moreover, our results showing an age-related increase of task-dependent activation within the DLPFC provide an important complement to its previously demonstrated reduced resting-state connectivity. We thus argue that reduced connectivity during rest and increased recruitment during active tasks may represent complementary mechanisms of age-related network changes. In contrast, activity in the left IPS correlates with behavioral incompatibility costs, rather than age, highlighting a critical distinction between these. Our behavioral and neural data jointly corroborate a significant influence of age on cognitive action control, which is neurobiologically differentiable from behavioral performance.